2014
DOI: 10.1002/pon.3558
|View full text |Cite
|
Sign up to set email alerts
|

Caregiving experiences predict changes in spiritual well-being among family caregivers of cancer patients

Abstract: Objective Although enhanced spiritual well-being has been linked to positive mental health outcomes among family caregivers of cancer patients, little is known regarding predictors of spiritual well-being in this population. The current study aimed to examine caregiving experiences as predictors of change in family caregivers’ spiritual well-being during the initial months following the patient’s cancer diagnosis. Methods Seventy family caregivers of newly diagnosed cancer patients (74% female, mean age = 59… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 47 publications
2
29
0
6
Order By: Relevance
“…Spiritual and religious beliefs appear in this context influencing how parents and families view their child's illness and handle this situation . Previous studies in the oncology field have shown that lower levels of SWB were associated with worse mental health and with lower levels of family support among cancer caregivers …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Spiritual and religious beliefs appear in this context influencing how parents and families view their child's illness and handle this situation . Previous studies in the oncology field have shown that lower levels of SWB were associated with worse mental health and with lower levels of family support among cancer caregivers …”
Section: Discussionmentioning
confidence: 99%
“…Since FCs of pediatric cancer patients are subjected to a stressful and vulnerable situation due to the uncertainty and the fear of loosing their children, they are at high risk of developing psychological problems as compared with other groups . In this scenario, religious struggles may appear as a reaction to this situation and might seriously compromise mental health and well‐being.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations